Profil Sensori Keripik Kentang Berdasarkan Check-All-That-Apply dan Ideal Profile Method - Krisjati, Paulina Gandhes Dian; Andarwulan, Nuri; Adawiyah, Dede Robiatul (Jurnal Teknologi dan Industri Pangan, 2025)
The snack industry has shown a stable increment for years and still has great potential for further increase. Potato chips rank second in sales volume in the snack industry, with an increase of 10.7% in 2022 compared to the previous year, propelling the manufacturers to compete in launching competitive  products in the market. To minimize the failure rate of new products, the knowledge of ideal sensory profile and attributes of potato chips is needed. Check-all-that-apply and ideal profile method are consumer perspective-based sensory profiling methods that provide a better understanding of a product’s sensory profile and ideal attributes. Three of the most consumed potato chips brands were used as benchmarks to determine the ideal sensory profile of potato chips with beef BBQ flavor. The result showed that the ideal attributes of potato chips consist of beef aroma and flavor, smokey aroma and flavor, savory taste, hardness, and crispness. These findings might help in developing more ideal-like potato chips and positively affecting consumers’ overall liking of the product. The result of sensory profile testing with consumers, particularly IPM, strongly correlated with the scoring attributes test conducted by selected panelists. There were sensory profile differences observed among the three samples used, which could be attributed to variations in raw materials and the processing technology used during production.